Yugoslavia : a unitary state or federation(conflicting historical tensions – one of the causes of the dissolution of Yugoslavia and the war in Croatia 1991-1996) - Davorin Rudolf (Zbornik Radova Pravnog Fakulteta u Splitu, 2009)
The authors present the idea of Yugoslavia as a federal state (Croatian view of a common state) and as a unitary and centralised one. The conflict between these two concepts actually occurred in the nineteenth century, shaped by the first ideas of a common state of South Slavs and lasted up until the dissolution of Yugoslavia in 1991.